Reconstructing Inca Socioeconomic Organization through Biography Analyses of Residential Houses and Workshops of Pucara de Tilcara (Quebrada de Humahuaca, Argentine) - Otero, Clarisa (2017)
Fil: Otero, Clarisa. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de Jujuy. Instituto de Ecorregiones Andinas; Argentina. Universidad Nacional de Jujuy. Instituto de Geología y Minería; Argentina. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto Interdisciplinario Tilcara; Argentina